TANGGUNG JAWAB DIREKSI PERUSAHAAN TERKAIT DENGAN AKSI MOGOK KERJA YANG DILAKUKAN OLEH PEKERJA - Nabila Tuffahati; Holyness N Singadimedja; Deviana Yuanitasari (IAIN Bengkulu, 2022)
Abstract: The company's directors as the organ that leads the company based on the law have the responsibility to manage the company for the benefit of the company and represent the company both inside and outside the court. Strike action is an activity that comes as a result of failed negotiations in resolving industrial relations disputes between companies and workers. Regarding the strike action, the Board of Directors as an organ that has responsibility for the company is also responsible. Therefore, this study aims to understand the responsibilities of the Board of Directors regarding strikes by workers and to find out what actions the company can take as an effort to prevent strikes by workers. This study uses a normative juridical approach, legal research conducted by examining literature or secondary data as the basis for research by conducting a search of regulations and literature. Based on research, the responsibilities of the Directors regarding the strike action are based on the provisions contained in the BUMN Law and the Company Law as well as the provisions in the Civil Code. The actions that can be taken as an effort to prevent strikes from affecting the company's productivity are by creating a harmonious relationship between the company and workers, establishing a Bipartite LKS, fulfilling workers' rights, and improving workers' welfare.